Model of Academics Professional Development Factors for Higher Education Institutions - Ali Elatawneh, Hebah Ahmed; Sidek, Safiah; Abo Mosali, Najmaddin (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents a study on developing a structural equation model of factors affecting UAE Academics Professional Development (APD) programs. Data used to develop the model was collected from questionnaire survey amongst three of UAE Higher Education Institutions. The model which comprised of seven independent constructs and one dependent construct was developed and assessed using AMOS SEM software. At the initial stage, eight measurement models (which is the eight constructs altogether) were developed and assessed individually using confirmatory factor analysis (CFA) of the software until it achieves goodness of fit. Then these eight measurement models are tied up into structural model which also assessed using CFA to find the goodness of fit. Once the structural model has achieved the goodness of fit, the path analysis or known as hypotheses testing was conducted on the model. The hypotheses testing found that five constructs have significant effect to academic’s professional development (APD) which are the i) design of teaching plan, ii) teaching skills, iii) communication skills, iv) expertise skill in the lesson content, and v) technology. While, two constructs which are i) individual and occupational identity and ii) policy and strategy do not have significant relationship with quality academic professional development. This model contributed to the body of knowledge and also to the related parties that involved in developing academic professional activities